Method of low-temperature rise of laser diode quality - Kamuz, A.M.; Oleksenko, P.Ph.; Kamuz, O.A.; Kamuz, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
In 1987 the authors of this article discovered the effect of irreversible gigantic modification (IGM) of semiconductors. Basing on the IGM phenomenon the authors have developed technological method that enables to considerably improve performances of laser diodes after their manufacturing by increasing power, slope efficiency, and decreasing threshold current. The technology has been tested on the laser diodes of several US companies. We obtained the same results in improvement of all the diodes from these companies. Performances of the laser diodes with small slope efficiency and high threshold current were improved using this modification. Slope efficiency of laser diodes was increased by 2.3 or 3.7 times and the threshold current was decreased from 15 % up to 29 %. It is shown that modification depth of the semiconductor chip for these laser diodes exceeds 50 microns. Shown is that a beam divergence of laser diode can be decreased using the irreversible gigantic modification.